An Analysis of Character Values in the Folklore of Bangka Belitung Paga and Si Penyumpit - Anita Puspita Sari; Maulina Hendrik; Agci Hikmawati (Proceedings Series on Social Sciences & Humanities, 2023)
This study aimed to describe the character values contained in Bangka Belitung’s folklore. This study was descriptive qualitative research. The data collection techniques used documentation and questionnaires. The data analysis technique used in this research was the Miles and Huberman method, namely data reduction analysis, data display, and conclusion drawing/verification. The data in this study were in the form of quotations that identify character values in the folklore book. The data source of this study was a story entitled Paga and Si Prnyumpit, which is contained in the Bangka Belitung folklore book by Sarman and Dwi Oktarina published by Azzagrafika in 2017. In this study, two Bangka Belitung folktales were analyzed, namely the story of Paga and Si Penyumpit. The results of the analysis in the Paga story are sentences that contain character values, namely 2 values of hard work character value, 1 value of social care character value, and 1 value of friendly character value. Furthermore, the story of Si Penyumpit contains sentences that contain character values, namely the character value of responsibility as much as 1 value, the value of social care character as much as 2 values, and the value of a peace-loving character as much as 1 value.